Simultaneous Analysis of Vibrations and Noise in the Task of Minimizing Vibroacoustic Activity of Machines - DĄBROWSKI, Zbigniew; DZIURDŹ, Jacek (Archives of Acoustics, 2016)
Simultaneous propagation of vibrations and noise has an important role in the task of minimizing vibroacoustic hazards on the station of operator of the construction machinery. In many cases vibrations transferred by the construction are processed to noise in different points of the machine. As a result, they may increase the level of noise at the workplace. The paper presents the proposition of a simple estimation of noise and vibration propagation paths of the machine. On the basis of the analysis of hydraulic excavator an effectiveness of a proposed procedure was shown. This procedure helps to minimize the transfer of vibrations of power unit in selected frequency ranges which led to the change of overall noise level in operator’s cab about 5 dB.